2002
DOI: 10.1103/physrevlett.88.070403
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Anomalous Spin-State Segregation in a Trapped Ultracold Vapor

Abstract: We observe counter-intuitive spin segregation in an inhomogeneous sample of ultra-cold, noncondensed Rubidium atoms in a magnetic trap. We use spatially selective microwave spectroscopy to verify a model that accounts for the differential forces on two internal spin states. In any simple understanding of the cloud dynamics, the forces are far too small to account for the dramatic transient spin polarizations observed. The underlying mechanism remains to be elucidated.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
225
2
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(240 citation statements)
references
References 17 publications
12
225
2
1
Order By: Relevance
“…In 2002, a group at JILA [6] showed that, in an trapped ultracold atomic gas of bosons, the ISRE can result in a spontaneous spatial "segregation" of two atomic internal states |1 and |2 (equivalent to a pseudo-spin 1/2). Several groups then proposed a theoretical explanation of these observations, using either one-dimensional spin 1/2 hydrodynamic [7] or kinetic [8,9] equations.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…In 2002, a group at JILA [6] showed that, in an trapped ultracold atomic gas of bosons, the ISRE can result in a spontaneous spatial "segregation" of two atomic internal states |1 and |2 (equivalent to a pseudo-spin 1/2). Several groups then proposed a theoretical explanation of these observations, using either one-dimensional spin 1/2 hydrodynamic [7] or kinetic [8,9] equations.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Quantum collisional effects can also produce spatiotemporal spin oscillations known as spin waves. In a recent experiment, we observed in an ultra-cold atomic gas a startling spin migration effect which we called "anomalous spin-state segregation" [3]. Several theory groups have shown that this effect can be thought of as a halfcycle of a large-amplitude, over-damped spin wave [4].…”
mentioning
confidence: 99%
“…The cumulative effect of many such spin-rotating collisions is such that inhomogeneities of spin propagate like waves rather than diffusively. The characteristic frequency scale for the spin rotation effect is the exchange collision rate, ω exch = 4πhan/m, where m, n, and a are the mass of the atoms, the number density, and the s-wave scattering length respectively.The experimental apparatus and spectroscopy method used to prepare and probe the ultra-cold gas are described in [3] and briefly will be summarized here. 87 Rb atoms are precooled and trapped in a magneto-optical trap, transferred to a Ioffe-Pritchard magnetic trap via a servo-controlled linear track, and cooled further using forced radio-frequency evaporation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, successes at loading atoms directly onto fabricated structures [2,3], evaporation in purely optical traps [4,5,6], and transport of atoms from one vacuum chamber to another [7,8,9] have created Bose-Einstein condensates (and in some cases degenerate gases of new species) in environments where enhanced optical access and proximity to surfaces allows for the discovery of new phenomena.…”
mentioning
confidence: 99%